FAKTOR-FAKTOR DAYA SAING INDUSTRI KECIL DAN MENENGAH (IKM) PERTENUNAN (Suatu Kasus pada IKM Pertenunan di Kecamatan Majalaya Kabupaten Bandung) - Eddy Guridno; Sugito Efendi (Universitas Nasional, 2020)
Simultaneously the source of competitive advantage in aspects of human resources, capital resources, technology, and competitive strategy has a significant effect on competitiveness. Competitive advantage in terms of human resources has a strategic and most significant influence on competitiveness compared to other variables. Relationships that are owned are directly proportional or positive. This means that the better the utilization and development of human resources owned by the company, the company's competitive position in the market will be stronger.